Human Resources Investment as an Introduction to improve the efficiency & activity of workers in E – Government - Abdul – Alrahman, Aladdin (Journal of Planner and Development, 2011)
The human resources are considered to be the main pillar of the organizations , economic development and the foundation of moving wheels of individual growth. This is considered as the basic tasks for any productive and economic activity . The investment of the human resources is the economic pillar of production , but the most important element of the production . This research tried to access the method of resource investment and to identify the problems and training as key element in establishment of E –government . A questionnaire document have been distributed to the workers at different levels in the colleges and institutes. The research concluded the necessity of job description , continuous training of the workers , using of modern equipments , legislative laws , in addition with the involvement of senior management in sessions to rehabilitation them , also to provide the necessary funds to buy the equipment and build the information network for each organization